The Legal Protection Towards Child Labour in an Attempt to Improve Their Work Safety and Health - Wiwi Yuhaeni (International Journal of Science and Society, 2020)
In Indonesia there now exist a lot of children who are forced work before their legal age allows so. With the number increasing, these children are mainly employed in the informal sector, which is not well-organized. It is estimated that there are some 2 to 4 million 14 – year-old children who are forced and moral condition. Child labour is almost always associated with poverty that widely prevails. Social welfare system devised by the government has not yet fully met the existing challenges. Protection towards children, which constitutes an important element of social welfare, is actually ensured by both the national and international labour law. The United Nations Organizations dealing with labour is the International Labour Organization, which-since its birt-has aimed to solve child labour problems. The problems identified are as follows, how is the legal protection towards children who forced to work, what is the employer’s responsibility towards child labour to ensure their work safety and health, and how is the supervition and control condacted by Office of Manpower and Transmigration towards child labour in the attempt to improve their safety and health. Legal protection provided by the government and employer towards children working at the Cibaduyut-based shoe-making industry is lacking, and children’s parents or poroxiest can not do anything to ensure that the children’s rights are fulfilled. The provision of working hours and wages does not conform to the existing labour law. The provision of working hours and wages does not conform to the existing labour law. As far as work break is concerned, some employers grand it to the child labour, while some others don’t. While the child labour are at work, the labour law states that day should be supervised by their parents or proxies, but in reality they are only watched by the employer. Supervision and control from the Office of Manpower and Transmigration towards child is apparently inadequate.